A Detailed Approach to Mechanical Design of Gas Pipeline Network System - Uzoma Mathew, Shadrack; A. Briggs, Tobinson (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
The developed optimization models for flow throughput and pressure drop along with gas pipeline network in the thesis titled, “Flow Optimization in Natural Gas Pipeline” confirmed lack in an economy in the operation of the inline compressors. The developed optimization models employed Panhandle-A equation as base the base equation. The work is a case study of pipelines of some oil producing companies in Nigeria. Further observed, there were increased flow throughput and a reduction in the overall line pressure drop. The nominal line diameter was 36” (0.9144m). The lack in the economy due to the cost of the compressors and the power consumed at the optimal level of performance triggered this work. The research work confirmed that saving in cost and operation of the inline compressors could only be achievable if the operating upstream/downstream pressure is more than the range 81—63bar at nominal pipe diameter of 36” (0.9144m). At nominal pipe diameters of 43” (1.0922m) and 50” (1.27m) economy in the operation of gas pipeline assets and facilities was attainable at upstream/downstream pressures over 81—63bar. The nominal pipe thickness is limited to 0.05m to 0.10m. The new design concepts give flexibility in design, material selection, and installation of gas pipeline network system.